Assessment of metabolic and mitochondrial dynamics in CD4+ and CD8+ T cells in virologically suppressed HIV-positive individuals on combination antiretroviral therapy - Masson, Jesse J. R. (2017)
Metabolism plays a fundamental role in supporting the growth, proliferation and effector functions of T cells. We investigated the impact of HIV infection on key processes that regulate glucose uptake and mitochondrial biogenesis in subpopulations of CD4+ and CD8+ T cells from 18 virologically-suppressed HIV-positive individuals on combination antiretroviral therapy (cART; median CD4+ cell count: 728 cells/μl) and 13 HIV seronegative controls. Mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) production were also analysed in total CD4+ and CD8+ T cells. Among HIV+/cART individuals, expression of glucose transporter (Glut1) and mitochondrial density were highest within central memory and naïve CD4+ T cells, and lowest among effector memory and transitional memory T cells, with similar trends in HIV-negative controls. Compared to HIV-negative controls, there was a trend towards higher percentage of circulating CD4+Glut1+ T cells in HIV+/cART participants. There were no significant differences in mitochondrial dynamics between subject groups. Glut1 expression was positively correlated with mitochondrial density and MMP in total CD4+ T cells, while MMP was also positively correlated with ROS production in both CD4+ and CD8+ T cells. Our study characterizes specific metabolic features of CD4+ and CD8+ T cells in HIV-negative and HIV+/cART individuals and will invite future studies to explore the immunometabolic consequences of HIV infection.